A novel simulation framework for crowd co-decisions. Issue 1 (2nd January 2020) - Yao, Xia; Sun, Hongbo; Fan, Baode
Abstract : Purpose: The purpose of this paper is to aim mainly at social public decision-making problems, studies the corresponding relationship between different voting rule combinations and the final results, and discusses the quantitative relationships between group intelligence (final votes) and individual intelligence (everyone) to defend democracy under the circumstance of rapid development of network technology, and crowd intelligence becomes more complicated and universal. Design/methodology/approach: After summarizing the crowd co-decisions of related studies, the standards, frameworks, techniques, methods and tools have been discussed according to the characteristics of large-scale simulations. Findings: The contributions of this paper will be useful for both academics and practitioners for formulating VV&A in large-scale simulations. Originality/value: This paper will help researchers solve the social public decision-making problems in large-scale simulations.